Coalescention of Water Oil Emulsions on the Surface of Ptfe Grains - D. Fazullin, Dinar; V. Mavrin, Gennady; A. Nasyrov, Ilnar; P. Sokolov, Mikhail (International Journal of Engineering and Technology, 2018)
In this work researches on division of water oil emulsions and oil-containing waste by a coalescention method on granular polymers from a polytetrafluoroethylene (PTFE) with sizes of particles of grains from 0,5 mm to 3 mm are conducted. Dynamic filtration of an emulsion was carried out through grains of polymer filled in a column with a diameter of 10 mm, the mass of grains of polymer was 2 g, and height of filling of a column of 10-12 cm. Speed of filtration of these emulsions through a column depends on the size of grains of a polytetrafluoroethylene. So with increase in the size of particles the speed of filtration increases, but the efficiency of removal of oil products decreases. Extent of cleaning of a water oil emulsion of oil products with initial concentration of 828 mg/dm3 made 62% at filtration through polymer with sizes of grains <0,5 mm and 51% at filtration of an emulsion through polymer grains with a size more than 3 mm. The efficiency of removal of free oil products was more than 90% of waste water. On the surface of grains of polymers the coalescention and aggregation of a particle of oil products is observed. Coalescention of oil products on grains of polymer is effective at removal from the unstable and stratified emulsions. Â